Plant Virus Emergence - Goodin, Michael; Verchot, Jeanmarie (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This compilation of articles elaborates on plant virus diseases that are among the most recent epidemiological concerns. The chapters explore several paradigms in plant virus epidemiology, outbreaks, epidemics, and pandemics paralleling zoonotic viruses and that can be consequential to global food security. There is evidence that the local, regional, national, and global trade of agricultural products has aided the global dispersal of plant virus diseases. Expanding farmlands into pristine natural areas has created opportunities for viruses in native landscapes to invade crops, while the movement of food and food products disseminates viruses, creating epidemics or pandemics. Moreover, plant virus outbreaks not only directly impact food supply, but also incidentally affect human health.